The Mediator Role of Organizational Justice in the Relationship between Teachers' Prejudices in their School Relations and Organizational Commitment: A Structural Equation Model - Tugba Hosgorur; Yahya Altinkurt; Duygu Kan (ÜNİVERSİTEPARK Limited, 2017)
This study aims to test the theoretical model developed for the mediator role of organizational justice in the relationship between teachers' prejudices in their school relations and organizational commitment levels. The research is designed using the survey model. The population comprised of teachers working at primary, secondary, and high schools in the Milas district of Mugla, Turkey, during the 2015-2016 academic year. The research sample comprised of 326 teachers selected through the disproportionate cluster sampling technique. The data for the research was collected through the Prejudices in School Relations Scale, Organizational Justice Scale, and the Organizational Commitment Scale. Pearson correlation coefficients were employed in terms of correlations between the variables observed during the research. The resulting model was tested using the Structural Equation Modeling (SEM). Research results show that teachers have a medium-level commitment, while their organizational justice perception is slightly over the medium level. Teachers are most prejudicial against managers and students, followed by parents, and least prejudicial against their colleagues. Teachers' prejudices against their colleagues are relatively low, while their prejudices against managers, students, and parents are close to the medium level. In this research, it was determined that teachers' organizational justice perception plays a mediator role between the variables of teachers' prejudices in their school relations and their organizational commitment. The intermediation of organizational justice perception displays a suppression effect in the inversely proportional relationship between teachers' prejudices and commitment.